Institutional Shape of Entrepreneurship in Poland - Ewa GRUSZEWSKA (Communications of International Proceedings, 2021)
Research background: Poland has recorded a noticeable decline in the percentage of business start-ups in recent years. The institutional environment is very important for entrepreneurship. Institutions create an environment that can encourage or inhibit entrepreneurial activity. Changes in institutions over time can contribute to entrepreneurial dynamism. The decline in entrepreneurship in Poland needs to be explained from the perspective of institutional factors. Purpose of the article: The aim of the research is to identify institutional determinants of entrepreneurship in Poland. The author’s attention is especially drawn to informal components of the institutional system that influence the development of entrepreneurship in Poland. Research methods: Indicators from GEM reports were used to analyze entrepreneurship in Poland compared to other countries. A comparison of institutional factors allowed to identify differences in the strength of their impact on entrepreneurship. Institutional factors influencing entrepreneurship were described on the basis of GEM reports, Doing Business reports, and the World Values Survey. The study period was taken as 2010-2020. Findings and added value: The falling rate of the number of people who start business is the result of deteriorating institutional conditions and the weakening of the incentives influencing entrepreneurial attitudes of Poles. The conducted research allowed to identify these factors. As far as entrepreneurial framework conditions are concerned, in Poland they are created by internal market dynamics and physical infrastructure, which – in case of this country – have a stronger impact than on average in other European states. Poles feel ready to be entrepreneurs, they perceive the opportunities offered by entrepreneurship, but they are afraid to take advantage of them. Fear of failure, a low level of trust, opportunism and traditionalism in undertaking economic activity seem to be the main characteristics of Poles which hinder their start in business. Hence, it is highly important to improve the image of an entrepreneur in the social consciousness of Poles.
Keywords: Entrepreneurship; Institutional Environment; Cultural Values; GEM